Understanding migration within countries: A global perspective - Maystadt, Jean-François; Peracchi, Silvia; Sargsyan, Ella; You, Liangzhi (International Food Policy Research Institute, 2024)
The majority of migrants remain within their own borders. While 281 million people have migrated in another country in 2020, the number of internal migrants is estimated to stand at around 763 million (UN DESA, 2016; IOM, 2021). At the global level, the existing literature has mainly focused on understanding the drivers of international migration (Karemera et al., 2000; Mayda, 2010; Kim and Cohen, 2010). Understanding the dynamics of internal migration is key for conjecturing future prospects in terms of poverty, food insecurity, urbanization, within-country inequalities and geopolitical instability.